A secondary distribution crack-resistant pure color brick and preparation method thereof
Through the preparation method of secondary fabrics, combined with ball milling and drying processes, the problem of insufficient strength of solid-color bricks in primary fabric pressing is solved, and high-strength and durable crack-resistant solid-color bricks are achieved.
Patent Information
- Application Number
- CN202410359374.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-27
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-03-27
AI Technical Summary
The existing solid-color bricks have low strength during the fabric pressing process, which can easily cause edge cracking and opening, and cannot meet the conditions where the strength requirements are high.
The preparation method of secondary fabric is adopted, sodium tripolyphosphate is added through ball mill to control the moisture and granule grading of powder, and then press it after being beaten with secondary fabric, and it is dried and dried in one go, combined with a specific sintering temperature. The change curve forms a brick blank with a base layer and a fabric layer.
It improves the strength, compactness and compressive resistance of the brick blank, avoids cracking and opening, and enhances the durability and sintering quality of the brick blank.
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic tiles, and in particular to a secondary-clothed anti-cracking pure-color tile and a preparation method thereof. Background Art
[0002] Ceramic tiles are a kind of material that can be used as floor decoration. They are made of clay and have various specifications. They are hard, pressure-resistant, wear-resistant, and moisture-proof. Some are glazed and have decorative effects. They are mostly used for the ground and floors of public and civil buildings. There are many varieties of floor tiles, and there is a lot of room for choice. According to the material, they can be divided into glazed tiles, full-body tiles, polished tiles, solid-color tiles, etc. Ceramic tiles, as a large-area paved floor material, use their own color and texture to create a different style of living environment;
[0003] Generally speaking, solid color bricks refer to ceramic tiles with only one color on the surface, no light and dark gradient, and a soft and smooth glaze. Solid color bricks have excellent stability and wear resistance. Whether used outdoors or indoors, the product can remain as good as new for a long time.
[0004] However, the solid color bricks in the prior art are generally made by pressing a single cloth. The moisture content of the powder used in the single cloth is often low, resulting in low strength of the bricks after being pressed by the press, which is prone to edge cracking and splitting, and cannot meet some occasions with high requirements for use strength.
[0005] Therefore, the prior art has defects and needs to be improved. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a crack-resistant solid color brick using secondary cloth with high strength and open edges that are not prone to edge cracking, and a preparation method thereof.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] A method for preparing a secondary distribution crack-resistant solid color brick comprises the following steps:
[0009] S1, mixing the base material blank and the surface material blank according to a predetermined ratio, and then putting them into a ball mill for ball milling;
[0010] During the ball milling process, 0.4wt% sodium tripolyphosphate was added, the ball milling time was 3-5h, and the ball milling fineness was 0.8-1.0% to obtain base material slurry and surface material slurry;
[0011] S2, subjecting the base material slurry and the surface material slurry to aging, iron removal, spray drying and sieving, respectively, to obtain base material powder and surface material powder;
[0012] The moisture content of the base powder is controlled at 6.3-6.8%, and the moisture content of the surface powder is controlled at 5.3-5.8%. The particle powder gradation of the two is: 20 mesh sieve material <0.5%, 60 mesh sieve material 65-85%;
[0013] S3, using a distribution system to distribute the base material powder and the surface material powder by double-distribution and then press-forming, and after demoulding, obtain a brick with a base material layer and a surface material layer;
[0014] S4. Send the bricks to the drying kiln for primary drying to make the moisture content in the bricks less than 0.8% of the total mass, and then apply glaze on the surface of the bricks with a glaze amount of 250-350g / m 2 ;
[0015] After secondary drying, it is sent to a roller kiln for firing at a temperature of 1170-1230°C for 50-55 minutes to obtain a secondary-clothed, crack-resistant solid-color brick.
[0016] S5, polishing, waxing, packaging and warehousing.
[0017] Using the above technical solution, in step S3, the mass ratio of the base material layer to the surface material layer is 7.2-8.4:1.
[0018] By adopting the above technical solution, in step S2, the moisture content of the base material powder is controlled at 6.4%, and the moisture content of the surface material powder is controlled at 5.6%.
[0019] Using the above technical solution, in step S3, the punching pressure of the brick is 310±10 bar, the number of punching times of a single machine is 4-5 times / min, and the thickness of the brick is controlled to be 9-12 mm.
[0020] Using the above technical solution, in step S4, the temperature of the second drying is 120-130°C.
[0021] Using the above technical solution, in step S1, the base material raw materials are composed of the following components by mass percentage: 12-24 parts of potassium sodium sand, 10-18 parts of bentonite, 6-12 parts of washed mud, 8-14 parts of diaspore powder, 6-8 parts of bauxite, 8-12 parts of magnesia clay, 4-8 parts of superplasticized mud and 3-6 parts of talc particles.
[0022] Using the above technical solution, in step S1, the fabric raw material is composed of the following components by mass percentage: 10-22 parts of potassium sodium sand, 7-12 parts of potassium sand, 8-14 parts of high white ball clay, 5-8 parts of medium white ball clay, 4-6 parts of bentonite, 4-8 parts of superplasticized clay, 2-3 parts of bauxite, 2-5 parts of talc particles and 0.2-1 part of whitening agent.
[0023] Using the above technical solution, in step S4, the glaze is composed of the following components by mass percentage: 14-28 parts of white stone powder, 6-10 parts of white jade, 6-12 parts of kaolin, 12-18 parts of calcined talc, 1-2 parts of aluminum oxide and 0.4-0.8 parts of titanium oxide.
[0024] Using the above technical solution, in step S4, the sintering temperature change curve is: from room temperature to 560°C, a heating rate of 32-48°C / min is adopted; from 560°C to the sintering temperature, a heating rate of 52-64°C is adopted, and the sintering temperature is maintained for 50-55 minutes; from the sintering temperature to 560°C, a cooling rate of 70-85°C / min is adopted; from 560°C to 150°C, a cooling rate of 42-54°C / min is adopted; after dropping to 150°C, it is naturally cooled to room temperature and taken out.
[0025] The present invention also provides a secondary-distribution crack-resistant solid-color brick, which is prepared by the method for preparing the secondary-distribution crack-resistant solid-color brick described in any of the above technical solutions.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention controls the moisture content of the base material powder to be 6.3-6.8% and the moisture content of the outer material powder to be 5.3-5.8%, so that appropriate bonding force can be formed between the powder particles, which is conducive to molding and pressing, and at the same time improves the strength of the brick blank and avoids edge cracking and edge splitting; and the base material powder and the outer material powder are pressed and molded by a positive secondary distribution through a distribution system, and a brick blank with a base material layer and an outer material layer is obtained after demolding; in this way, the base material powder and the outer material powder can be more closely combined, the density and strength of the brick blank are increased, and the compression resistance and durability of the brick blank are improved; in addition, the whole body material of the pure color brick is divided into a base material layer and an outer material layer, and because the whole body becomes a secondary distribution, the amount of screening used is significantly reduced, which makes the transportation process The agglomerated powder in the process can be better screened out, thereby solving the problem of a large amount of powder agglomerates remaining in the screening of the fabric at one time; when preparing the slurry, adding 0.4wt% of sodium tripolyphosphate for ball milling can promote the dispersion and suspension of the particles, so that the particles in the base material blank and the surface material blank are more evenly dispersed in the water to form a more stable slurry, and sodium tripolyphosphate can react with the hydroxyl groups on the surface of the particles during the ball milling process to form chemical bonds, increase the bonding force between the particles, and thus improve the viscosity and stickiness of the slurry; during the sintering process of the brick blank, the heating and cooling processes of the brick blank can be balanced through a specific temperature change curve, and the temperature change and stress distribution of the brick blank can be controlled, thereby improving the sintering quality, stability and crack resistance of the brick blank. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0029] The present invention provides a method for preparing a secondary distribution crack-resistant pure color brick, comprising the following steps:
[0030] S1. The base material blank and the outer material blank are respectively mixed in a predetermined ratio, and then respectively put into a ball mill for ball milling; during the ball milling process, 0.4wt% of sodium tripolyphosphate is added, the ball milling time is 3-5h, and the ball milling fineness is 0.8-1.0% to obtain a base material slurry and an outer material slurry; sodium tripolyphosphate can promote the dispersion and suspension of particles during the ball milling process, prevent particle aggregation and precipitation, and make the particles in the base material blank and the outer material blank more evenly dispersed in the water to form a more stable slurry, and sodium tripolyphosphate can react with the hydroxyl groups on the surface of the particles during the ball milling process to form chemical bonds, thereby increasing the bonding force between the particles, thereby increasing the viscosity and stickiness of the slurry, so that the slurry after ball milling is easier to form a uniform brick blank.
[0031] S2. After the base material slurry and the surface material slurry are aged, iron removed, spray dried and sieved, the base material powder and the surface material powder are obtained respectively; wherein, the moisture content of the base material powder is controlled at 6.3-6.8%, and the moisture content of the surface material powder is controlled at 5.3-5.8%, and the particle powder gradation of the two is: 20 mesh sieve upper material <0.5%, 60 mesh sieve upper material 65-85%; in the process of preparing bricks, the moisture content of the powder is an important factor, and the right amount of moisture can form appropriate bonding force between the powder particles, which is conducive to the molding and pressing process. If the moisture content is too high, it is easy to cause the powder to be too thin, difficult to mold, and the bricks are easy to deform or crack; if the moisture content is too low, the strength of the pressed bricks is low, which is easy to cause edge cracking and opening.
[0032] S3. The base material powder and the surface material powder are pressed and formed by the distribution system through the secondary distribution. After demoulding, a brick with a base material layer and a surface material layer is obtained. In this way, the base material powder and the surface material powder can be more closely combined together, thereby increasing the density and strength of the brick. Through appropriate pressure and molding process, a higher brick strength can be obtained, and the compression resistance and durability of the brick can be improved.
[0033] S4. Send the bricks to the drying kiln for primary drying to make the moisture content in the bricks less than 0.8% of the total mass, and then apply glaze on the surface of the bricks with a glaze amount of 250-350g / m 2 ; Then, after secondary drying, it is sent to a roller kiln for firing at a firing temperature of 1170-1230°C and a firing time of 50-55min to obtain a secondary-clothed, crack-resistant solid-color brick; primary drying can reduce the moisture content in the brick blank so that the subsequent glazing and firing processes can proceed smoothly. Specifically, the moisture in the brick blank will evaporate during the firing process to form steam. If the moisture content in the brick blank is too high, the release of steam may be uneven, resulting in uneven pressure distribution inside the brick blank, thereby causing cracking or deformation. By performing primary drying, the moisture in the brick blank can be evenly evaporated, reducing the internal stress during the firing process and improving The sintering quality and crack resistance of the brick blank; during the glazing process, if the surface of the brick blank contains too much moisture, it will affect the adhesion and curing effect of the glaze. Through primary drying, the moisture on the surface of the brick blank can be controlled so that the subsequent glazing can achieve the expected effect; secondary drying is the second drying process of the brick blank after glazing. Its function is to evaporate the moisture on the surface of the glazed brick blank, so that the glaze can fully solidify and adhere to the surface of the brick blank, so that the glaze forms a hard surface and is firmly bonded to the surface of the brick blank. In addition, secondary drying can also reduce the risk of deformation and cracking of the brick blank during the firing process, and improve the quality and crack resistance of the brick blank.
[0034] S5. Polishing, waxing, packaging and warehousing; Polishing refers to the polishing of the surface of the brick to obtain a smooth and flat surface. By using grinding tools and abrasives, the unevenness and defects on the surface of the brick are removed to make it have a better look and feel; Waxing is the process of coating the surface of the brick with wax. The wax can increase the gloss of the brick surface and play a protective role to prevent stains and moisture penetration.
[0035] Furthermore, in step S3, the mass ratio of the base material layer to the surface layer is 7.2-8.4:1; the mass ratio of the base material layer to the surface layer can affect the uniformity of the brick blank. A higher proportion of the base material layer can provide better support and stability, thereby improving the uniformity and strength of the brick blank structure. The surface layer is relatively light and can adapt to the shrinkage of the brick blank and the stress during sintering, reducing the possibility of cracking.
[0036] Furthermore, in step S2, the moisture content of the base powder is controlled at 6.4%, and the moisture content of the outer powder is controlled at 5.6%. Controlling the moisture content of the base powder and the outer powder at this parameter can improve the fluidity and mixing properties of the powder, facilitate uniform dispersion and mixing of various ingredients, and avoid problems such as agglomeration, stratification or uneven mixing.
[0037] Furthermore, in step S3, the punching pressure of the brick blank is 310±10bar, the number of single-machine punching times is 4-5 times / min, and the thickness of the brick blank is controlled to be 9-12mm; appropriate punching pressure and number of times can improve the density and uniformity of the brick blank. By applying sufficient punching pressure, a tighter bond can be formed between the base material layer and the surface layer, reducing the presence of pores and voids. At the same time, multiple punching can further improve the density of the brick blank, ensuring that the structure of the entire brick blank is uniform.
[0038] Furthermore, in step S4, the temperature of the second drying is 120-130°C; a higher temperature can cause the water in the brick to evaporate, thereby reducing the moisture content of the brick. In the drying process of the brick, the evaporation of water is a key step, which can promote the shrinkage and structural stabilization of the brick. By setting the temperature within the range of 120-130°C, faster evaporation of water can be achieved while maintaining the structural stability of the brick.
[0039] Further, in step S1, the base material raw materials are composed of the following components in mass percentage: 12-24 parts of potassium sodium sand, 10-18 parts of bentonite, 6-12 parts of washed mud, 8-14 parts of diaspore powder, 6-8 parts of bauxite, 8-12 parts of magnesia clay, 4-8 parts of superplasticized mud and 3-6 parts of talc particles. Sodium potassium sand is a kind of ore containing sodium and potassium, which can provide the basic structure and stability of bricks and enhance the strength and durability of bricks; bentonite is a kind of clay mineral with water absorption and cementing properties, which can increase the plasticity and plasticity of bricks and absorb water to form colloid, thereby improving the plasticity and formability of bricks; washed mud is clay that has been washed with water, and the impurities and particles in it are removed, thereby providing a purer clay component and improving the quality of bricks; diaspore powder and bauxite are a kind of fine powder aluminum ore, which can increase the strength and refractory properties of bricks, react to form sintering products during the sintering process of bricks, and enhance the density and high temperature resistance of bricks; talcum granules are a kind of talc ore with a certain particle size, which can improve the refractory and thermal stability of bricks.
[0040] Further, in step S1, the fabric raw material is composed of the following components in mass percentage: 10-22 parts of potassium sodium sand, 7-12 parts of potassium sand, 8-14 parts of high white ball clay, 5-8 parts of medium white ball clay, 4-6 parts of bentonite, 4-8 parts of superplastic clay, 2-3 parts of bauxite, 2-5 parts of talc particles and 0.2-1 part of brightener; high white ball clay and medium white ball clay are clay minerals with high whiteness, which can provide whiteness and glossiness of the fabric layer, improve the appearance quality of the fabric layer, and make it have better appearance and decorative effect; and the brightener is an additive used to improve the whiteness and glossiness of the fabric, which can improve the appearance quality of the fabric and make it brighter.
[0041] Further, in step S4, the glaze is composed of the following components by mass percentage: 14-28 parts of white stone powder, 6-10 parts of white jade corundum, 6-12 parts of kaolin, 12-18 parts of burnt talc, 1-2 parts of aluminum oxide and 0.4-0.8 parts of titanium oxide. White stone powder is a fine powder quartz ore, which can provide whiteness and glossiness of the glaze; white jade corundum is an ore with high hardness and glossiness, which can increase the hardness and wear resistance of the glaze; kaolin is a clay mineral with water absorption and cementation, which can increase the cohesion and adhesion of the glaze, so that the glaze can better adhere to the surface of the brick, providing better coating effect and durability; titanium oxide is an additive with white pigment effect, which can improve the whiteness and hiding power of the glaze.
[0042] Further, in step S4, the sintering temperature change curve is: from room temperature to 560°C, a heating rate of 32-48°C / min is adopted; from 560°C to the sintering temperature, a heating rate of 52-64°C is adopted, and the sintering temperature is maintained for 50-55 minutes; from the sintering temperature to 560°C, a cooling rate of 70-85°C / min is adopted; from 560°C to 150°C, a cooling rate of 42-54°C / min is adopted; after dropping to 150°C, it is naturally cooled to room temperature and taken out. From room temperature to 560℃, use a heating rate of 32-48℃ / min. This stage is the initial heating process of the brick. A slower heating rate can avoid too fast temperature changes in the brick during the heating process, thereby reducing the thermal stress on the surface and inside of the brick, which is conducive to uniform heating of the brick and avoiding cracking; from 560℃ to the firing temperature, use a heating rate of 52-64℃, and keep at the firing temperature for 50-55min: This stage is the main sintering process of the brick. Using a moderate heating rate and holding time can promote crystallization and densification inside the brick, improve High mechanical strength and crack resistance of bricks; from firing temperature to 560℃, a cooling rate of 70-85℃ / min is adopted. This stage is the cooling process of the bricks. A faster cooling rate can help the bricks to quickly dissipate heat and reduce the thermal stress generated during the sintering process, which is beneficial to the stability of the bricks and avoid cracking; from 560℃ to 150℃, a cooling rate of 42-54℃ / min is adopted. This stage is the further cooling process of the bricks. A moderate cooling rate can control the cooling speed of the bricks and avoid thermal stress caused by too fast temperature changes.
[0043] The present invention also provides a secondary-distribution crack-resistant solid-color brick, which is prepared by the secondary-distribution crack-resistant solid-color brick preparation method described in the above technical solution.
[0044] Example 1
[0045] Embodiment 1 of the present invention provides a method for preparing a secondary distribution anti-cracking solid color brick, comprising the following steps:
[0046] S1. The base material blank and the surface material blank are respectively prepared in a predetermined ratio, and then respectively put into a ball mill for ball milling; during the ball milling process, 0.4wt% of sodium tripolyphosphate is added, the ball milling time is 3h, and the ball milling fineness is 0.8% to obtain a base material slurry and a surface material slurry;
[0047] The base material raw materials are composed of the following components by mass percentage: 24 parts of potassium sodium sand, 18 parts of bentonite, 6 parts of washed mud, 14 parts of aluminum stone powder, 6 parts of bauxite, 12 parts of magnesia clay, 8 parts of superplastic mud and 3 parts of talc particles;
[0048] The fabric raw material is composed of the following components by mass percentage: 22 parts of potassium sodium sand, 7 parts of potassium sand, 14 parts of high white ball clay, 5 parts of medium white ball clay, 6 parts of bentonite, 4 parts of superplasticized clay, 2 parts of bauxite, 2 parts of talc particles and 1 part of whitening agent;
[0049] S2. After the base material slurry and the surface material slurry are aged, iron removed, spray dried and sieved, base material powder and surface material powder are obtained respectively; wherein the moisture content of the base material powder is controlled at 6.4%, the moisture content of the surface material powder is controlled at 5.6%, and the particle powder gradation of the two is: 20 mesh sieve upper material <0.5%, 60 mesh sieve upper material 65-85%;
[0050] S3, using a distribution system to distribute the base material powder and the surface material powder by positive secondary distribution and then press molding, and after demolding, a brick blank having a base material layer and a surface material layer is obtained; wherein the mass ratio of the base material layer to the surface material layer is 7.2:1, the punching pressure of the brick blank is 310±10bar, the number of single-machine punching is 4 times / min, and the thickness of the brick blank is controlled to be 12mm;
[0051] S4. Send the bricks to the drying kiln for primary drying to make the moisture content in the bricks less than 0.8% of the total mass, and then apply glaze on the surface of the bricks with a glaze amount of 250g / m 2 ;
[0052] The glaze is composed of the following components by mass percentage: 14 parts of white stone powder, 6 parts of white jade, 12 parts of kaolin, 12 parts of calcined talc, 1 part of aluminum oxide and 0.4 parts of titanium oxide;
[0053] Then it is secondary dried and sent to a roller kiln for firing. The second drying temperature is 120°C; the firing temperature is 1230°C, and the firing time is 55 minutes, so that the crack-resistant solid color bricks with secondary distribution are obtained; during the firing process, the firing temperature change curve is: from room temperature to 560°C, a heating rate of 48°C / min is used, from 560°C to the firing temperature, a heating rate of 52°C is used, and the firing temperature is maintained for 55 minutes; from the firing temperature to 560°C, a cooling rate of 70°C / min is used; from 560°C to 150°C, a cooling rate of 54°C / min is used; after dropping to 150°C, it is naturally cooled to room temperature and taken out.
[0054] S5, polishing, waxing, packaging and warehousing.
[0055] Example 2
[0056] A method for preparing a secondary distribution crack-resistant solid color brick comprises the following steps:
[0057] The following steps are involved:
[0058] S1, mixing the base material blank and the surface material blank according to a predetermined ratio, and then putting them into a ball mill for ball milling;
[0059] During the ball milling process, 0.4 wt% sodium tripolyphosphate was added, the ball milling time was 5 h, and the ball milling fineness was 1.0% to obtain a base material slurry and a surface material slurry;
[0060] The base material raw materials are composed of the following components by mass percentage: 12 parts of potassium sodium sand, 10 parts of bentonite, 6 parts of washed mud, 8 parts of aluminum stone powder, 6 parts of bauxite, 8 parts of magnesia clay, 4 parts of superplastic mud and 6 parts of talc particles;
[0061] The fabric raw material is composed of the following components by mass percentage: 10 parts of potassium sodium sand, 12 parts of potassium sand, 14 parts of high white ball clay, 8 parts of medium white ball clay, 4 parts of bentonite, 4 parts of superplastic clay, 3 parts of bauxite, 5 parts of talc particles and 1 part of whitening agent;
[0062] S2, subjecting the base material slurry and the surface material slurry to aging, iron removal, spray drying and sieving, respectively, to obtain base material powder and surface material powder;
[0063] The moisture content of the base powder is controlled at 6.3%, and the moisture content of the surface powder is controlled at 5.3%. The particle powder gradation of the two is: 20 mesh sieve material <0.5%, 60 mesh sieve material 65-85%;
[0064] S3, using a distribution system to distribute the base material powder and the surface material powder by positive secondary distribution and then press molding, and after demolding, obtain a brick blank having a base material layer and a surface material layer; wherein the mass ratio of the base material layer to the surface material layer is 8.4:1, the punching pressure of the brick blank is 310±10bar, the single machine punching times is 5 times / min, and the thickness of the brick blank is controlled to be 9mm;
[0065] S4. Send the bricks to the drying kiln for primary drying to make the moisture content in the bricks less than 0.8% of the total mass, and then apply glaze on the surface of the bricks with a glaze amount of 350g / m 2 ;
[0066] The glaze is composed of the following components by mass percentage: 14 parts of white stone powder, 6 parts of white jade, 6 parts of kaolin, 12 parts of calcined talc, 1 part of aluminum oxide and 0.4 parts of titanium oxide;
[0067] Then it is secondary dried and sent to a roller kiln for firing. The second drying temperature is 130°C; the firing temperature is 1170°C, and the firing time is 50 minutes, so that the crack-resistant solid color bricks with secondary distribution are obtained; during the firing process, the firing temperature change curve is: from room temperature to 560°C, a heating rate of 32°C / min is adopted, from 560°C to the firing temperature, a heating rate of 64°C is adopted, and the firing temperature is maintained for 50 minutes; from the firing temperature to 560°C, a cooling rate of 85°C / min is adopted; from 560°C to 150°C, a cooling rate of 54°C / min is adopted; after dropping to 150°C, it is naturally cooled to room temperature and taken out.
[0068] S5, polishing, waxing, packaging and warehousing.
[0069] Comparative Example 1
[0070] The method for preparing the crack-resistant solid-color bricks with secondary distribution of this comparative example 1 is different from that of Example 1 in that: in step S1, sodium tripolyphosphate is not added during the ball milling process.
[0071] Comparative Example 2
[0072] The method for preparing the crack-resistant solid color bricks with secondary cloth of this comparative example 2 is different from that of example 1 in that: in step S2, the moisture content of the base material powder is controlled at 4.8%, and the moisture content of the surface material powder is controlled at 4.2%.
[0073] Comparative Example 3
[0074] The method for preparing the crack-resistant solid color bricks with secondary distribution of this comparative example 3 is different from that of Example 1 in that in step S4, after applying the glaze, no secondary drying is performed.
[0075] Comparative Example 4
[0076] The method for preparing the crack-resistant solid-color bricks with secondary cloth of comparative example 4 is different from that of example 1 in that in step S3, the mass ratio of the base material layer to the surface material layer is 5.2:1.
[0077] Comparative Example 5
[0078] The method for preparing the crack-resistant solid-color bricks with secondary distribution of this comparative example 5 is different from that of Example 1 in that: in step S1, the base material raw material does not contain bentonite.
[0079] Comparative Example 6
[0080] The method for preparing the crack-resistant solid-color bricks with secondary distribution in Comparative Example 6 is different from that in Example 1 in that in step S1, the base material raw material does not contain diaspore powder and bauxite.
[0081] Comparative Example 7
[0082] The method for preparing the crack-resistant solid-color bricks with secondary distribution of this comparative example 7 is different from that of Example 1 in that: in step S4, the surface glaze does not contain kaolin.
[0083] Comparative Example 8
[0084] The preparation method of the crack-resistant solid-color bricks with secondary distribution in this comparative example 8 is different from that in Example 1 in that: in step S4, the firing temperature change curve is: from room temperature to 1230°C, a heating rate of 92°C / min is adopted; from 1230°C to room temperature, a cooling rate of 24°C / min is adopted.
[0085] The following experiments are conducted on the above-mentioned Examples 1-2 and Comparative Examples 1-8 to verify or understand their performances.
[0086] Serial number Mechanical strength Refractoriness ≥℃ Number of edge cracks or damage defects of kiln products / 100 pieces Example 1 44MPa 1856 0 Example 2 42MPa 1852 1 Comparative Example 1 36MPa 1843 4 Comparative Example 2 28MPa 1828 9 Comparative Example 3 37MPa 1827 2 Comparative Example 4 32MPa 1842 4 Comparative Example 5 36MPa 1834 6 Comparative Example 6 40MPa 1678 2 Comparative Example 7 38MPa 1742 6 Comparative Example 8 31MPa 1784 5
[0087] Table 1 Comparison of crack-resistant solid color brick performance tests of secondary cloth in various embodiments and comparative examples
[0088] According to Table 1 above, the crack-resistant solid color bricks with secondary distribution prepared in Example 1 and Example 2 control the moisture content of the base material powder to 6.3-6.8% and the moisture content of the surface material powder to 5.3-5.8%. In this way, appropriate bonding force can be formed between the powder particles, which is conducive to molding and pressing, and at the same time improves the strength of the brick blank to avoid edge cracking and edge opening. In addition, the base material powder and the surface material powder are pressed and molded by the distribution system after secondary distribution, and a brick blank with a base material layer and a surface material layer is obtained after demolding. In this way, the base material powder and the surface material powder can be more closely combined, the density and strength of the brick blank are increased, and the compression resistance and durability of the brick blank are improved. In addition, the whole body material of the solid color brick is divided into a base material layer and a surface material layer. Because the whole body becomes a secondary distribution material, the amount of screening used is significantly reduced, so that the powder agglomerated during transportation can be better screened out, thereby solving the problem of a large amount of powder agglomerates remaining in the screening of the first distribution material.
[0089] In Comparative Example 1, sodium tripolyphosphate can promote the dispersion and suspension of particles during the ball milling process, prevent the aggregation and precipitation of particles, and make the particles in the base material blank and the surface material blank more evenly dispersed in the water to form a more stable slurry. In addition, sodium tripolyphosphate can react with the hydroxyl groups on the surface of the particles during the ball milling process to form chemical bonds, thereby increasing the bonding force between the particles, thereby improving the viscosity and stickiness of the slurry, making it easier for the slurry after ball milling to form a uniform brick blank;
[0090] In Comparative Example 2, when preparing the brick, the moisture content of the powder is an important factor. The right amount of moisture can form a proper bonding force between the powder particles, which is beneficial to the molding and pressing process. If the moisture content is too low, not only is molding difficult, but the strength of the brick obtained by pressing is also low, which is easy to cause edge cracking and splitting.
[0091] In comparative example 3, secondary drying is the second drying process of the brick after glazing, and its function is to evaporate the moisture on the surface of the brick after glazing, so that the glaze can be fully solidified and attached to the surface of the brick, so that the glaze forms a hard surface and is firmly combined with the surface of the brick. In addition, secondary drying can also reduce the risk of deformation and cracking of the brick during the firing process, and improve the quality and crack resistance of the brick;
[0092] In comparative example 4, the mass ratio of the base material layer and the surface material layer can affect the uniformity of the brick. A higher ratio of the base material layer can provide better support and stability, thereby improving the uniformity and strength of the brick structure. The surface material layer is relatively light and can adapt to the shrinkage of the brick and the stress during sintering, reducing the possibility of cracking.
[0093] In comparative example 5, bentonite is a clay mineral with water absorption and cementing properties, which can increase the plasticity and formability of the brick, and can absorb water to form a colloid, thereby improving the plasticity and formability of the brick; washed mud is clay that has been washed with water, and impurities and particles therein are removed, thereby providing a purer clay component and improving the quality of the brick;
[0094] In Comparative Example 6, aluminum ore powder and bauxite are fine powder aluminum ore, which can increase the strength and refractory properties of the brick, react to form sintered products during the sintering process of the brick, and enhance the compactness and high temperature resistance of the brick;
[0095] In Comparative Example 7, kaolin is a clay mineral with water absorption and cementing properties, which can increase the cohesion and adhesion of the glaze, so that the glaze can be better attached to the surface of the brick, providing better coating effect and durability;
[0096] In Comparative Example 8, a too fast heating rate may cause structural damage to the ceramic tile, and a high-speed heating rate may increase the thermal stress inside the tile body, thereby causing crack formation or abnormal crystal growth, reducing the strength and stability of the ceramic tile. In addition, a too fast heating rate may also lead to insufficient gas release inside the tile body, forming pores, and reducing the density and quality of the ceramic tile; when the cooling rate is too slow, the molten phase may recrystallize at a lower temperature, resulting in structural damage and abnormal crystal growth, thereby reducing the density and quality of the ceramic tile.
[0097] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a crack-resistant solid color brick with secondary distribution, characterized in that: The following steps are involved: S1, mixing the base material blank and the surface material blank according to a predetermined ratio, and then putting them into a ball mill for ball milling; The base material raw materials are composed of the following components by mass percentage: 12-24 parts of potassium sodium sand, 10-18 parts of bentonite, 6-12 parts of washed mud, 8-14 parts of aluminum stone powder, 6-8 parts of bauxite, 8-12 parts of magnesia clay, 4-8 parts of superplasticized mud and 3-6 parts of talc particles; During the ball milling process, 0.4wt% sodium tripolyphosphate was added, the ball milling time was 3-5h, and the ball milling fineness was 0.8-1.0% to obtain base material slurry and surface material slurry; S2, subjecting the base material slurry and the surface material slurry to aging, iron removal, spray drying and sieving, respectively, to obtain base material powder and surface material powder; The moisture content of the base powder is controlled at 6.4%, and the moisture content of the top powder is controlled at 5.6%. The particle gradation of the two powders is: 20-mesh sieve material <0.5%, 60-mesh sieve material 65-85%; S3, using a distribution system to distribute the base material powder and the surface material powder by positive secondary distribution and then press molding, and after demoulding, obtain a brick with a base material layer and a surface material layer, wherein the mass ratio of the base material layer to the surface material layer is 7.2-8.4:1; S4. Send the bricks to the drying kiln for primary drying to make the moisture content in the bricks less than 0.8% of the total mass, and then apply glaze on the surface of the bricks with a glaze amount of 250-350g / m 2 The glaze is composed of the following components by mass percentage: 14-28 parts of white stone powder, 6-10 parts of white jade, 6-12 parts of kaolin, 12-18 parts of calcined talc, 1-2 parts of aluminum oxide and 0.4-0.8 parts of titanium oxide; Then, after secondary drying, it is sent to a roller kiln for firing, the firing temperature is 1170-1230℃, the firing time is 50-55min, and the firing temperature change curve is: from room temperature to 560℃, a heating rate of 32-48℃ / min is adopted, from 560℃ to the firing temperature, a heating rate of 52-64℃ is adopted, and the firing temperature is maintained for 50-55min; from the firing temperature to 560℃, a cooling rate of 70-85℃ / min is adopted; from 560℃ to 150℃, a cooling rate of 42-54℃ / min is adopted; after dropping to 150℃, it is naturally cooled to room temperature and taken out to obtain a secondary distribution anti-cracking solid color brick; S5, polishing, waxing, packaging and warehousing.
2. The method for preparing the crack-resistant solid color bricks with secondary distribution according to claim 1, characterized in that: In step S3, the punching pressure of the brick is 310±10 bar, the punching times of a single machine is 4-5 times / min, and the thickness of the brick is controlled to be 9-12 mm.
3. The method for preparing the crack-resistant solid color bricks with secondary distribution according to claim 1, characterized in that: In step S4, the temperature of the second drying is 120-130°C.
4. The method for preparing the crack-resistant solid color bricks with secondary distribution according to claim 1, characterized in that: In step S1, the fabric raw material is composed of the following components by mass percentage: 10-22 parts of potassium sodium sand, 7-12 parts of potassium sand, 8-14 parts of high white ball clay, 5-8 parts of medium white ball clay, 4-6 parts of bentonite, 4-8 parts of superplasticized clay, 2-3 parts of bauxite, 2-5 parts of talc particles and 0.2-1 part of whitening agent.
5. A secondary-clothed anti-crack solid-color brick, characterized in that: The brick is prepared by the method for preparing the crack-resistant solid-color brick with secondary cloth as described in any one of claims 1 to 4.
Citation Information
Patent Citations
High-strength secondary distribution ceramic tile and preparation method thereof
CN115594484A